Wide bandwidth arbitrary phase difference branch line coupler. Issue 9 (September 2017) - Qamar, Zeeshan; Chan, Wing Shing; Derek, Ho
Abstract: As a conventional branch line coupler (BLC) is limited to a phase difference of 90°, different phases have typically been realized by cascading additional phase‐shifters, which inevitably increase the circuit size. This article presents a BLC capable of achieving a combined wide bandwidth and arbitrary phase difference. This is achieved by inserting a phase compensation network directly in each of the series branch lines, which effectively modifies the electrical lengths. A prototype 60°/–120° coupler has been fabricated and experimentally characterized to achieve a 0.5‐dB magnitude imbalance, 5° phase stability, return loss better than −15 dB, and isolation better than −14 dB from 2.3 to 3.5 GHz.